Surgical Management of Abdominal Tuberculosis: Experience from a Tertiary-Care Center (Medical Forum Monthly, 2020)
Objective: To evaluate the role of surgery in the management of abdominal tuberculosis.Study Design: Abdominal tuberculosis study.Place and Duration of Study: This study was conducted at the Department of Surgery Unit-II, Peoples University of Medical and Health Sciences, Nawabshah, and Department of Surgery, Suleman Roshan Medical College Hospital, Tandoadam, from January 2017to December 2019.Materials and Methods: Cases were analyzed in terms of demography, clinical features, investigations, operative treatment, and outcome. The data was collected on a structured proforma, analyzed statistically and the results were tabulated.Results: During study period 39 cases of abdominal tuberculosis were operated, comprising 22 (56.4%) male and 17 (43.6%) female, majority 14 (35.9%) patients were in age group ranged between 12-20 years, 79.5% of population was belonging to low socioeconomic status. The clinical presentation of 69.2% patients was revealing features of peritonitis, followed by acute intestinal obstruction in 30.8% cases; ileal perforation was the commonest intra-operative finding in 43 % of cases followed by multiple small bowel perforations in 20.5% of cases. The most frequent surgical procedure applied was ileostomy in 41 % of cases followed by resection anastomosis in 17.4%of cases. The complications were observed in 7cases, in which the most frequent one was the surgical site infection which was observed in 05 cases. The overall hospital stay observed was 7 to 38 days with a mean of 17 days. 38 patients were discharged after recovery on anti-tubercular therapy, and one patient was expired during immediate post-operative management period. The follow up was observed in 22 cases for a period of 12 weeks to 48 weeks. Conclusion: Early "diagnosis is the important factor to prevent systemic and local complications of intestinal tuberculosis. In emergency cases, without delay surgical exploration and attentive care is met with good recovery. Resection-anastomosis in the form of right hemi-colectomy or segmental resection has largely been adopted instead of simple bypass of obstructive lesions with good result".